Wilson Fonseca: crendices e lendas amazônicas para canto e piano - AZULAY , Humberto Valente (Universidade Federal do Pará, 2017)
This paper discusses Wilson Fonseca, one of the most important composers of our Amazon region, due to its history and dedication of a lifetime for music and our culture, being a reference not only in the music field, but also in memory and redemption of history and culture of Santarem. Amazonian legends and superstitions for voice and piano, a topic addressed in this research, is just one of many faces which portrayed the author in his extensive music production.